FENOMENA FEAR OF MISSING OUT (FOMO) SEBAGAI ALAT PEMASARAN: STUDI PADA INDUSTRI KULINER - Erislan Erislan (LPPM Politeknik Pratama, 2025)
The phenomenon of Fear of Missing Out (FOMO) has become an increasingly common marketing strategy in the culinary industry, especially in today’s visually driven and fast- paced social media landscape. This study aims to analyze how culinary businesses implement FOMO strategies and how they impact the consumption behavior of young consumers. The research employed a qualitative descriptive approach with case studies in Yogyakarta and Bandung. Data were collected through in-depth interviews with six culinary business owners and twelve young consumers active on social media, along with observation of promotional content and customer interactions. The findings reveal that business owners deliberately use various FOMO techniques such as limited-time offers, seasonal exclusive menus, influencer collaborations, and viral visual narratives to create urgency and emotional appeal. On the other hand, consumers tend to make purchases due to social pressure and the fear of missing out on trends rather than actual needs. FOMO strategies are proven effective in encouraging short-term impulse buying but do not necessarily foster long-term customer loyalty. These findings suggest that FOMO can be a powerful marketing tool when combined with product quality and authentic customer experiences.